The impact of alcohol-related risk-taking behaviour on younger driver deaths in the Western Cape Province: a retrospective cross-sectional study - Gerber, Carmen (Department of Public Health and Family Medicine, 2022)
Drunk driving is a public health threat, endangering the lives of all road users. Younger drivers are inclined to engage in risk-taking behaviour, such as drunk driving with BAC levels exceeding the legal limit. The prevalence of drunk driving in the country has increased among the youth, with children starting to drink alcohol under the age of 13 year in the country. In the Western Cape province, alcohol consumption and risk-taking behaviour were prevalent among school-going children. Younger drivers (15 to 19 years) had the highest driver mortality rates per registered driver, compared to older drivers in the province. Graduated driver license (GDL) programmes provide a supervised learning opportunity for younger drivers to gain driving skills and include a zero-alcohol tolerance restriction. The usefulness of implementing a GDL programme in the country needs to be explored. It is therefore important to understand the impact of alcohol-related risk-taking behaviour among younger drivers. This retrospective cross-sectional study measured alcohol-attributable crash risk by age and sex, from a sample of 921 driver fatalities from Western Cape mortuary records (2009 to 2011). Poisson regression was used to ascertain whether the mortality risk profile for young drivers was differentially affected by alcohol. Female drivers aged 15 to 24 years with zero or low BAC levels (<0.05 g/100ml) were the reference category. Statistical significance was set at p< 0.05. The median age for all driver deaths in the sample was 37 years (IQR 27-49), with 820 males representing 89% of the sample. BAC levels tested among 351 driver fatalities represented 38.1% of the study sample. The median BAC level among all tested driver deaths was zero, with more than half of the sample having BAC levels less than 0.05 g/100ml. The median age for 150 driver deaths with BAC levels ≥ 0.05 g/100ml, was 32.5 years (IQR 26–42). Among 140 male driver deaths testing positive for alcohol, the median BAC level was 0.18 (IQR 0.13- 0.23) and among ten female drivers 0.2 g/100ml (0.11-0.21). Male drivers were five times more likely to die from a fatal alcohol-related crash (IRR 5.02; p< 0.001; 95% CI: 3.86-6.53). The relative mortality rate was highest among drivers aged 25 to 34 years (IRR 1.54; 95%CI 1.43-1.66; p< 0.001). The findings from this study highlights the need for continued and improved BAC surveillance and indicates the need for the broader application of alcohol interventions and development of a GDL programme.